2018
DOI: 10.4103/jfmpc.jfmpc_185_17
|View full text |Cite
|
Sign up to set email alerts
|

Household food security in an urban slum: Determinants and trends

Abstract: Introduction:As we are moving from millennium development goals to sustainable development goals, food insecurity is imposing a formidable challenge to the policymakers, especially in developing countries such as India. A survey conducted in the urban slum areas of Vellore district, 6 years back, had reported food insecurity as high as 75%. The current study was a resurvey to assess the food security status in the aforementioned area.Materials and Methods:A community-based survey was conducted in which data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…However, food insecurity prevalence was lower in the present study compared with similar developing countries such as Iran (59.1%) and the Philippines (65%) [10]. Correlates of food insecurity identified in our study were consistent with existing literature—showing that being female, having less than a high school education, working for fewer hours, and having large family sizes were predictors of food insecurity [10, 22].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, food insecurity prevalence was lower in the present study compared with similar developing countries such as Iran (59.1%) and the Philippines (65%) [10]. Correlates of food insecurity identified in our study were consistent with existing literature—showing that being female, having less than a high school education, working for fewer hours, and having large family sizes were predictors of food insecurity [10, 22].…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, study participants reporting that their employment needs were met, were also likely to be food insecure, although this was not significant in the multivariable analysis (OR = 1.134, 95% CI: 0.592, 2.172, p = 0.726). Prior studies have shown that employment-related food insecurity among the urban poor has a lot to do with the patterns of employment amongst urban poor slum dwellers [10, 2224]. The finding that study participants with partially and fully met employment needs were likely to be food insecure suggests that being employed may not be fully reflective of income capacity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations